2018
DOI: 10.3389/fonc.2018.00372
|View full text |Cite
|
Sign up to set email alerts
|

Geographic Disparities in Previously Diagnosed Health Conditions in Colorectal Cancer Patients Are Largely Explained by Age and Area Level Disadvantage

Abstract: Background: Geographical disparity in colorectal cancer (CRC) survival rates may be partly due to aging populations and disadvantage in more remote locations; factors that also impact the incidence and outcomes of other chronic health conditions. The current study investigates whether geographic disparity exists amongst previously diagnosed health conditions in CRC patients above and beyond age and area-level disadvantage and whether this disparity is linked to geographic disparity in CRC survival.Methods: Dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…After removing duplicates and non-original articles, 2,926 studies were identified, of which 109 were retained for full-text screening. A total of 73 articles were excluded following full-text review or qualitative synthesis, 34 …”
Section: Resultsmentioning
confidence: 99%
“…After removing duplicates and non-original articles, 2,926 studies were identified, of which 109 were retained for full-text screening. A total of 73 articles were excluded following full-text review or qualitative synthesis, 34 …”
Section: Resultsmentioning
confidence: 99%
“…Geographical health disparities have created social vulnerabilities that have led to disasters. “Geographical health disparities are thought to be due, not only to limited physical access to health care, but also to differences in demography, attitudes, lifestyle factors, and cultural practices in regional and rural settings” (Goodwin et al, 2018). Social vulnerability refers to: (1) the susceptibility of a social group to potential negative impacts such as economic losses and human suffering caused by external stresses on humans as well as (2) their capacity to recover from the impacts of hazards (Armas & Gavris, 2013; Blaikie et al, 2014; Cannon, 1994; Cutter & Emrich, 2006; Deyle et al, 1998; Godschalk, 1991; Mitchell, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…demography, attitudes, lifestyle factors, and cultural practices in regional and rural settings" (Goodwin et al, 2018).…”
mentioning
confidence: 99%